Analisis Permintaan Pendidikan Tinggi Pada Anak di Kecamatan Kamang Baru Kabupaten Sijunjung - Febria Rahim (Universitas Negeri Padang, 2019)
This research aims to analyze (1) Effect of Education Costs on Higher Education Demand for Children in Kamang Baru Sub-district, (2) Effect of Parental Education Level on Higher Education Demand for Children in Sub-Districts Kamang Baru, (3) The influence of the desire to work in the modern sector of the demand for higher education in children in the Kamang Baru sub-district, (4) the influence of the desire to obtain high income towards the demand for higher education in children in the Kamang Baru sub-district, (5) the influence of the social status of the community on demand for higher education in children in the district of Kamang Baru. The study population of this research is families with children who had graduated from high school in Kamang Baru sub-district. The sampling technique is multistage random sampling with a total sample of 92. Data analysis techniques using multiple regression analysis with the significance test of the t test and F. The results showed that (1) Education costs had a significant negative effect on the demand for higher education in children. (2) The level of parental education has a significant effect on the demand for higher education in children ( 3) The desire to work in the modren sector significantly influences the demand for higher education in children, (4) The desire to obtain high income has a significant effect on the demand for higher education in children (5) Public social status significantly influence the p Higher education demand for children.